If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + -2 = -11 + 9t Reorder the terms: -2 + 6t = -11 + 9t Solving -2 + 6t = -11 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. -2 + 6t + -9t = -11 + 9t + -9t Combine like terms: 6t + -9t = -3t -2 + -3t = -11 + 9t + -9t Combine like terms: 9t + -9t = 0 -2 + -3t = -11 + 0 -2 + -3t = -11 Add '2' to each side of the equation. -2 + 2 + -3t = -11 + 2 Combine like terms: -2 + 2 = 0 0 + -3t = -11 + 2 -3t = -11 + 2 Combine like terms: -11 + 2 = -9 -3t = -9 Divide each side by '-3'. t = 3 Simplifying t = 3
| 2t-13=-4+t | | -5u(u-8)(u+1)=0 | | (6-y)(2y-7)=0 | | (w+8)(w+1)=0 | | 3x^2+27x-5.5=0 | | 10r+10=70 | | 4a-2a-7+6= | | 6x+16=2+x+16 | | x+3y-5z=12 | | -25x^2+45x-18=0 | | x^2/9-y^2/16=0 | | p=220/(6.75*3.25) | | 36s^2-25g^2=0 | | 6x+6=95 | | (4+u)(5u+8)=0 | | 6x+6=55 | | 6x^2-2x-8= | | 0=21 | | X=7(r+3)(r-14) | | 4x^3-20x^2+16x= | | (B^3-4b^2)+(-4bI+16)= | | 5(m+1)=3(2m-2) | | rc+rx+bc+bx=0 | | 43+x=6+3x | | 20m^2+25m^3= | | 16+7x=-40 | | 20*20-90+40= | | 5x^2-39x+29=0 | | Z=8(x+h) | | 0.00000458=(x^2)/3.9 | | 4.58*10^-6=[2x]^2/[3.9-x] | | X^2+85x-13800=0 |